Implementasi Ekstrakurikuler Bahasa Inggris No What-What English Party di SDN 3 Tanggunggunung - Elyziah Tri Nurcahyanti; Yasip Yasip (Jurnal Simki Postgraduate, 2024)
The purpose of this study was to describe the No What-What English Party extracurricular program at SDN 3 Tanggunggunung. Using qualitative research methods of the case study type. The subjects of this research were extracurricular supervisors, principals, and grade V students.Using data collection techniques of observation, interview, and documentation. The data analysis technique used the Miles and Huberman model. Based on the results of the study, 1) program planning is based on the Pancasila Student Profile, namely Global Diversity, 2) program implementation is carried out outside the classroom every Saturday, consisting of introductory, core, and closing activities, 3) evaluation is carried out once a month and assessment in the form of descriptions.